Valuation at Origination of Legal Prepayment Options Embedded in 15-Year German Mortgage Loans - Jan Henrik Wosnitza (Credit and Capital Markets – Kredit und Kapital, 2018)
Section 489 of the German Civil Code anchors a prepayment option in all fixed-rate retail loans with a term of more than 10.5 years. The primary purpose of this paper is to develop an approach for valuing legal prepayment options (LPOs), embedded in 15-year German mortgage loans, at their origination. The analysis is based on 11,201 pairs of 10-and 15-year German mortgage rates that cover the period from June 2001 until February 2018 in steps of one month. In order to value the LPOs, trajectories of 10-year German mortgage rates are simulated by means of the exponential Vasicek model. The exercise strategy of the borrowers is a main driver of the value of LPOs. Our simulation results reveal that the following exercise strategy maximizes the average value of the LPOs under investigation (from the perspective of the day of their origination): On average, borrowers should exercise their LPOs, embedded in 15-year German mortgage loans, and refinance either if the present value of interest savings is at least 1.2 % of the outstanding loan amount or if the prevailing refinancing rate is, first, below the 15-year mortgage rate and, second, close to its presumed floor of 0.1 %. – – Bewertung gesetzlicher Rückzahlungsoptionen in 15-jährigen Hypothekenkrediten am Tag ihrer Emission Nach Paragraph 489 des Bürgerlichen Gesetzbuchs haben Darlehnsnehmer das Recht, Darlehnsverträge mit gebundenem Sollzinssatz nach frühestens 10,5 Jahren ohne Vorfälligkeitsentschädigung vorzeitig zurückzuzahlen. Das Hauptziel des vorliegenden Aufsatzes besteht darin, ein Verfahren zur Bewertung von gesetzlichen Rückzahlungsoptionen, die 15-jährigen Hypothekenkrediten anhaften, am Tag ihrer Emission zu entwickeln. Die Analyse basiert auf 11.201 Paaren von 10- und 15-jährigen Hypothekenzinsen, die den Zeitraum von Juni 2001 bis Februar 2018 in monatlichen Schritten abdecken. Zur Bewertung des Rechts auf vorzeitige Rückzahlung werden 10-jährige Hypothekenzinsen mit Hilfe des exponentiellen Vasicek Models simuliert. Die Ausübungsstrategie der Kreditnehmer hat einen großen Einfluss auf den Wert der gesetzlichen Rückzahlungsoption. Unsere Simulationsergebnisse zeigen, dass die folgende Ausübungsstrategie den durchschnittlichen Wert der gesetzlichen Rückzahlungsoption (aus der Perspektive des Emissionstags) maximiert: Im Durchschnitt sind Darlehnsnehmer gut damit beraten ihren 15-jährigen Hypothekenkredit vorzeitig zu kündigen und zu refinanzieren, entweder wenn die Zinsersparnisse mindestens 1,2 % der noch ausstehenden Kreditsumme betragen oder wenn der Refinanzierungszins erstens unter dem 15-jährigen Hypothekenzins und zweitens in der Nähe seiner angenommenen Untergrenze von 0,1 % liegt. Abbreviations: Cumulative distribution function (CDF), Legal prepayment option (LPO), Probability of default (PD).
Keywords: D14; G12; G21; 330; Constant default intensity; Exponential Vasicek model; Mortgage loan; Mortgage rate; Prepayment option; Refinancing